Mercado imobiliário e política urbana no Distrito Federal: Um índice de preços de imóveis para o Distrito Federal - Vicente Correia Lima Neto (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This work presents the construction of a local price index for the Federal District Real Estate market. The main objective of this local price index is to help build a real estate observatory, using data from the real estate transaction from the Secretariat of Finance of the Federal District. The index was developed using the Stratified Central Tendency methodology for the following spatial basis- the Federal District, the Administrative Region and the Territorial Planning Unit - TPU. By comparison with a national real estate index the study concludes that the local index by UPT is the closest to the national price index behavior.
Keywords: R30; R32; R38; 330; real estate market; real estate index; Federal District